ปัจจัยที่ส่งผลต่อความความสำเร็จของเกษตรอินทรีย์ในชุมชนเกษตรกรรายย่อย จังหวัดนครสวรรค์ - มณีโชติ, สวรรค์; อธินุวัฒน์, ดุสิต (Thai Journal of Science and Technology, 2019)
Abstract This study aimed to study success impacts on organic farming in small farmer community, PGS organic lover group, Chum Ta Bong district, Nakhon Sawan province, who have passed participatory guarantee system (PGS) standard certification. The data were collected by questionnaire and in-depth interview. Questions included attitudes, knowledge of organic farming standard, organic farming standard practice problems, social factor and economic factor. Results showed that all the small farmers in PGS organic lover group gained more organic farming standard knowledge and certification system from training program and the best practice in the area. They did the best way for organic farming process in the farm followed national organic standard, Organic Thailand. They showed 93 % positive attitude to organic farming that could make the very good health for human and nature. Organic farming reduced the production cost. Even though, 40 % of their own land location was not suitable for organic farming, but the problem was solved under the standard frame. Social factor and economic factor highly supported 100 and 80 % of them to do organic farming for example using family labors. Moreover, family members and government agreed with doing organic farming. However, 40 % of them still need supporting from the government such as budget and organic production factors. Keywords: PGS organic lover group; Chum Ta Bong; PGS; organic farming folk way; guarantee by the community